Image analysis from TEM and AFM micrograph, Table S1, S2, S3, Figure S1, Figure S2 - Enikö Kádár; Andrew Fisher; Björn Stolpe; Roy M Harrison; Francesco Parello; Jamie Lead (PANGAEA, 2013)
We report on metal enrichment along a natural pH gradient owing to increased CO2 degassing at cold, shal- low seeps of Vulcano Island in the Mediterranean Sea, off Sicily. We assessed composition of unfiltered and filtered seawater (b100 nm) along acidic zones ranging between ambient and pH 5, and showed that most seep derived elements are present as nanoclusters which then aggregate into larger colloids while mixing with ambient seawater along a pH gradient. Size and elemental composition of such naturally occurring nanoparticles assessed by modern characterisation methods were in good agreement with the results from conventional analytical methods. We provide analytical evidence for the presence in the water column of a large fraction of seep derived ele- ments (e.g. approximately 50% of iron, over 80% of Mn, 100% of Cr, S and Zn) in the form of nano sized par- ticles (e.g. b100 nm) even at typical open ocean pHs. We launch in situ sampling protocols and sample preparation procedures for multi-method suitable to obtain accurate measurements on nanoparticles from environmental samples. Based on our results a first insight to the formation of natural nanoparticles at cold CO2 seeps is presented and the persistence of such nano-clusters in the surrounding seawater is stipulated.
Supplement to: Kádár, E et al. (2012): Metallic nanoparticle enrichment at low temperature, shallow CO2 seeps in Southern Italy. Marine Chemistry, 140, 24-32, https://doi.org/10.1016/j.marchem.2012.07.001